Implementasi Murabahah untuk Pembiayaan Modal Kerja (Studi Kasus Bank Syariah Indonesia KCP Pati Kutoharjo ) - Runindyo, Andi Septiana; Pujiyono, Arif (Musyarakah: Journal of Sharia Economic (MJSE), 2024)
This research discusses the implementation of murabahah financing as working capital at BSI KCP Pati Kutoharjo. The background of this study is based on the discrepancy in the use of murabahah financing, which should be for trade transactions but is applied for working capital. The research method used is qualitative with a case study approach. Data were collected through interviews, observations, and documentation from BSI staff and customers. The results show that BSI KCP Pati Kutoharjo has a high percentage in channeling murabahah financing for working capital. These findings highlight the importance of transparency and compliance with sharia principles in every banking transaction. The conclusion of this study suggests the need for revision and evaluation of the use of murabahah contracts at BSI to ensure conformity with sharia principles